First report of Rhodnius montenegrensis (Hemiptera: Reduviidae: Triatominae) in Bolivia - Menezes, André Luiz Rodrigues [UNESP]; Schneider, Ricardo Angelo; Ribeiro, Mariane Albuquerque Lima [UNESP]; Dos Santos, Cícera Alexsandra Costa; de Carvalho, Elaine Oliveira Costa; Vilardi, Gabriel Cestari; de Oliveira, Jader; da Rosa, João Aristeu [UNESP] (FapUNIFESP (SciELO), 2022)
Background: The subfamily Triatominae, which comprises 157 species, carries the protozoan Trypanosoma cruzi, the etiological agent of Chagas disease. This short communication reports for the first time the occurrence of Rhodnius montenegrensis in Bolivia. Methods: Active searches were carried out on palm trees of the genus Oenocarpus in Beni district, Bolivia. Results: Fifteen R. montenegrensis specimens were collected from a rural area of the Beni district, Bolivia, and tested positive for T. cruzi. Conclusions: This new report expands the geographic distribution of the species in Latin America. Due to their ability to transmit trypanosomatids, the species deserves the attention of vector control programs.
Keywords: Entomological surveillance; Kissing bugs; New record; Western Amazon